Experimental Herpes Simplex Virus Type 1 Encephalitis: Treatment with 5-Trifluoromethyl-2′-Deoxyuridine - Clough, D. W. (1977)
5-Trifluoromethyl-2′-deoxyuridine (F(3)dThd) was evaluated for its neurotoxicity and for its ability to increase the life span of mice injected intracerebrally with herpes simplex virus type 1 (HSV-1) and F(3)dThd simultaneously. F(3)dThd showed no neurotoxicity at the highest concentration tested (100 mg/kg). Mice injected intracerebrally with HSV-1 died within 5 days postinfection. However, all mice injected concurrently with HSV-1 and 100 mg of F(3)dThd per kg lived through the termination of the experiment (60 days). Protection of mice from HSV-1 encephalitis by F(3)dThd has been shown to be dose dependent, with 100, 75, 50, and 25 mg of F(3)dThd per kg yielding a survival rate of 100, 90, 50, and 10%, respectively. HSV-1 titers in mouse brains receiving HSV-1 and 100 mg of F(3)dThd per kg concurrently were 100- to 1,000-fold lower at 2 to 4 days postinfection than control mice receiving HSV-1 alone. F(3)dThd was shown not to stimulate interferon production. Encephalitis caused by a ribonucleic acid virus, encephalomyocarditis virus, was not modified by F(3)dThd treatment.